Talak Tiga Perspektif Hukum Perkawinan Indonesia: Kritik Terhadap Representasi Dalam Film Talak 3 (2016) - Neilta Melkiati (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This article discusses the direct triple talak found in the film entitled Talak 3 (2016) with criticism and analysis based on the views of conventional scholars and positive law applicable in Indonesia. The film that directed by Hanung Bramantyo and Ismail Basbeth has crucial issues that must be noticed regarding to it practice. The purpose of this study is to analyze the concept of triple talak and to provide constructive criticism of the law representative in film Talak 3 (2016). The approach used in this study is juridical-normative. The object of the research is the Film Talak 3 (2016), with references to Indonesian positive law in the form of the Compilation of Islamic Law (KHI) and Law Number 1 of 1974 concerning Marriage, and references to Islamic law in the form of the opinions of the imams of the madzhab al-arba’ah, and classical ulama’ that have a different perspective. Apart from the differences in views of the ulama' regarding talak ba'in kubra which is imposed all at once, Indonesian positive law does not explicitly mention this, but in Article 120 of the KHI it is stated that talak ba'in kubra is a divorce that occurs for the third time. Talak ba'in kubra divorce that is pronounced all at once is not included in the category of divorce that is carried out in stages, so that the imposition of talak ba'in kubra divorce all at once is deemed invalid because according to this article, the imposition of talak ba'in kubra divorce must occur in stages. The imposition of a triple divorce means that former couples cannot reconcile unless the woman first marries another man (Muhallil) and then divorces after the dukhul. As conveyed in the film Talak 3 (2016), talak ba’in kubra is raised as part of the storyline, but is not accompanied by an in-depth exploration of its legal practice, and the legal and social consequences attached to this practice. The practice carried out is talak ba’in kubra which is imposed at once, and the legal and social consequences faced after talak ba’in kubra cause both parties to prepare the most perfect scenario possible in order to be able to remarry. This scenario of course involves many parties who also face difficulties.